The gospel of the son of God an introduction to Matthew - Bauer, David R. (Downers Grove, Illinois IVP Academic, an imprint of InterVarsity Press, 2019)
Form and genre -- Approach and method -- Circumstances of composition -- Shape of composition -- Interpretation of Matthew 1:1-4:16 -- Interpretation of Matthew 4:17-16:20 -- Interpretation of Matthew 16:21-28:20 -- Jesus: the Christological titles -- Jesus: additional aspects of Christology -- God -- Salvation history and eschatology -- Discipleship.
"From beginning to end, the Gospel of Matthew emphasizes that Jesus is the Son of God. In this comprehensive introduction to Matthew, David Bauer presents a holistic inductive approach with a literary, theological, and canonical focus. Exploring issues of genre, interpretive methods, authorship, audience, and literary structure, he also guides readers through interpretation and emerging theological themes"--
Includes bibliographical references and index
Keywords: Bible -- Introductions